Fertilization management with sewage sludge sustains Eucalyptus productivity in Cerrado infertile soil - Cardoso, Paulo Henrique Silveira; Neto, Aníbal Deboni; Oliveira, Fernando Carvalho; Tomazello-Filho, Mario; Guedes, Fernanda Trisltz Perassolo; Alvares, Clayton Alcarde [UNESP]; Stape, Jose Luiz [UNESP]; Nogueira, Thiago Assis Rodrigues [UNESP]; Capra, Gian Franco; Jani, Arun Dilipkumar; He, Zhenli; Abreu-Junior, Cassio Hamilton (Elsevier, 2022)
Sewage sludge (SS) application to Eucalyptus urograndis plantations can result in wood yields rivalling those achieved when mineral fertilizers are used. While climatic conditions determine Eucalyptus growth and wood production, the use of fertilizers containing boron (B) can mitigate the impact of drought on Eucalyptus growth. We hypothesized that SS application supplemented with P and B would improve growth and wood production of Eucalyptus planted in the Cerrado region of Brazil. We evaluated wood production and the influence of two years of meteorological seasonality on trunk cross-sectional area (TCSA) growth of Eucalyptus planted on an infertile Oxisol treated with SS. The experiment was conducted on a 54-month-old Eucalyptus urograndis plantation. The treatments were: i) control; ii) two levels of mineral fertilization; iii) seven SS treatments with or without P and/or B. SS application, based on tree N requirement, supplemented with P, resulted in wood production like those produced under mineral fertilization. Within climate variables, rainfall, potential evapotranspiration, and minimum air temperature had the largest influence on Eucalyptus TCSA growth. There was lower accumulated TCSA growth in the cold and dry winter season compared to the hot and rainy summer. However, SS application supplemented with B promoted TCSA growth, enhancing Eucalyptus tolerance to drought periods. In summary, SS supplemented with P and B is a valuable option as an organomineral fertilization management in Eucalyptus plantations, as it improved trunk growth during drought periods as well as wood volume production.
Keywords: Climatic condition; Forest management; Organic by-products; Solid waste management